Pneumococcal Hydrogen Peroxide–Induced Stress Signaling Regulates Inflammatory Genes - Loose, Maria (J Infect Dis, 2015)
Microbial infections can induce aberrant responses in cellular stress pathways, leading to translational attenuation, metabolic restriction, and activation of oxidative stress, with detrimental effects on cell survival. Here we show that infection of human airway epithelial cells with Streptococcus pneumoniae leads to induction of endoplasmic reticulum (ER) and oxidative stress, activation of mitogen-associated protein kinase (MAPK) signaling pathways, and regulation of their respective target genes. We identify pneumococcal H(2)O(2) as the causative agent for these responses, as both catalase-treated and pyruvate oxidase-deficient bacteria lacked these activities. Pneumococcal H(2)O(2) induced nuclear NF-κB translocation and transcription of proinflammatory cytokines. Inhibition of translational arrest and ER stress by salubrinal or of MAPK signaling pathways attenuate cytokine transcription. These results provide strong evidence for the notion that inhibition of translation is an important host pathway in monitoring harmful pathogen-associated activities, thereby enabling differentiation between pathogenic and nonpathogenic bacteria.